Alpha-Lipoic Acid Attenuates Cerebral Ischemia and Reperfusion Injury via Insulin Receptor and PI3K/Akt-Dependent Inhibition of NADPH Oxidase - Yinhua Dong; Hongxin Wang; Zefeng Chen (International Journal of Endocrinology)
Alpha-lipoic acid (ALA) has various pharmacological effects such as antioxidative, anti-inflammatory, and antiapoptotic properties. In the present study, administration of ALA (40 mg/kg, i.p.) for 3 days resulted in a significant decrease in neuronal deficit score and infarct volume and a significant increase in grip time and latency time in Morris water maze at 48 h after middle cerebral artery occlusion and reperfusion (MCAO/R) in rats. ALA also reduced the increased TUNEL-positive cells rate and the enhanced caspase-3 activity induced by MCAO/R. However, the underlying mechanisms remain poorly understood. In this study, we found that ALA could activate insulin receptor and PI3K/Akt signaling pathways, inhibit the expression and activity of NADPH oxidase, and subsequently suppress the generation of superoxide and the augment of oxidative stress indicators including MDA, protein carbonylation, and 8-OHdG. In conclusion, ALA attenuates cerebral ischemia and reperfusion injury via insulin receptor and PI3K/Akt-dependent inhibition of NADPH oxidase.